0754 Cognitive Behavioral Therapy for Hypersomnia (CBT-H): A Feasibility Study for Improving Health-Related Quality of Life. (27th May 2020) - Ong, J C; Dawson, S C; Mundt, J M; Adkins, E; Moore, C
Abstract: Introduction: The purpose of this study was to conduct a feasibility trial for a novel cognitive behavioral therapy (CBT-H) aimed at improving health-related quality of life (HRQoL) in people with hypersomnia. Methods: Participants were 35 adults (32 female, mean age=32.0 years, SD=12.9) with an established diagnosis of Narcolepsy Type 1 (n=12), Type 2 (n=11), or Idiopathic Hypersomnia (n=12). Participants were assigned to individual (n=19) or group (n=16, 3-5 per group) format of a 6-session, manualized CBT-H, delivered using live videoconferencing. Key components of CBT-H included structuring daytime behaviors (e.g., planned naps), emotion regulation techniques, and energy management strategies. Outcome measures for HRQoL included PROMIS measures for depression, anxiety, self-efficacy, and social isolation. Other clinical outcome measures included the Patient Health Questionnaire (PHQ) and Epworth Sleepiness Scale (ESS). Exit interviews were used to collect qualitative data to inform acceptability of the intervention. Results: Intent-to-treat analyses were conducted on the entire sample with the last observation carried forward for 3 participants who did not provide post-treatment data. Paired-samples t-test revealed a significant reduction on PROMIS depression (t[34]=2.05, p=0.0486, d =-0.35), and significant increases on PROMIS general self-efficacy (t[34]=3.64, p=0.0009, d =0.62) and self-efficacy managing social interactions (t[34]=2.14, p=0.0396, d =0.36). Significant reductions were also observed on the ESS (t[34]=2.07, p=0.0458, d =-0.35) and PHQ (t[34]=4.42, p<.0001, d =-0.75). Mixed-design ANOVAs revealed no significant differences on hypersomnia diagnosis or treatment format. Qualitative data supported the acceptability of telehealth delivery with mixed opinions regarding the format and number of sessions. Conclusion: These findings support the acceptability of a novel CBT-H delivered using a telehealth model and the feasibility of reducing excessive sleepiness and improving HRQoL, particularly in the domains of self-efficacy and depression, in people with narcolepsy and idiopathic hypersomnia. Support: This study was supported by grant 185-SR-17 from the American Sleep Medicine Foundation.